Exploration of Pathogenic Microbes and Antagonistic Agents in Apple Production Centers in Malang Regency - Abadi, Abdul Latief; Choliq, Fery Abdul; Trianti, Irisa; Maknunin, Lu'lu'il; Yulianti, Novi Dwi (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2024)
The apple farming group is one of the built of Department of Plant Pests and Diseases, Agricultural Faculty, Brawijaya University. In 2019, this departmen received a request from apple farmers in Madiredo Village, Pujon District to held an assistance programs of apple cultivation and environmentally pest control. This is related with the increasing of fruit rot and other diseases which is caused a decrease of apple production especially in Malang Regency. In general, apple farmers still rely on disease control using chemical fungicides which can have a negative impact on the environment and create resistance to pathogenic fungi. Therefore, this research was carried out to explore and study the potential of biological agents in apple production centers in Malang Regency, specifically in Poncokusumo, Pujon, and Batu District on conventional fields and mixed fields. This research was held observationally through fields surveys and farmer interviews, took soil samples and disease samples then then isolating, identifying and testing for antagonism at laboratory. Based on interviews and observation of symptomology, two dominant diseases were found, namely fruit rot disease (Gloeosporium sp.) and marsonina leaf spot disease (Marssonina coronaria). The results of exploration of the rhizospheric apple plants obtained isolates on conventional fields in Kec. Pujon has the highest abundance of fungal colonies compared to other regions. Based on the results of the antagonism test for pathogenic fungi and biological agents, it was found that the isolate codes KH.C, KK.A, JK.B, JK.J, and BK.B had the highest percentage of inhibition or the most effective in controlling the pathogen Gloeosporium sp. So in the next, the species can be identified molecularly.